2015
DOI: 10.1111/exd.12601
|View full text |Cite
|
Sign up to set email alerts
|

Periostin induces fibroblast proliferation and myofibroblast persistence in hypertrophic scarring

Abstract: Hypertrophic scarring is characterized by the excessive development and persistence of myofibroblasts. These cells contract the surrounding extracellular matrix resulting in the increased tissue density characteristic of scar tissue. Periostin is a matricellular protein that is abnormally abundant in fibrotic dermis, however, its roles in hypertrophic scarring are largely unknown. In this report, we assessed the ability of matrix-associated periostin to promote the proliferation and myofibroblast differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 55 publications
2
49
0
Order By: Relevance
“…These results suggested that overexpressed miR-185 can inhibit HSFBs growth and that the underlying mechanism was mediated, at least partly, through the suppression of TGF-β1 and Col-1 expression. HS occurs as a result of a pathological wound-healing process, characterized by excess collagen deposition and hyperproliferation of fibroblasts (2,6,8). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that overexpressed miR-185 can inhibit HSFBs growth and that the underlying mechanism was mediated, at least partly, through the suppression of TGF-β1 and Col-1 expression. HS occurs as a result of a pathological wound-healing process, characterized by excess collagen deposition and hyperproliferation of fibroblasts (2,6,8). …”
Section: Discussionmentioning
confidence: 99%
“…These cells contract the surrounding extracellular matrix resulting in the increased tissue density characteristic of scar tissue, which not only affects the appearance and functions of skin, however can additionally result in psychological trauma for the patient (2). The treatment of pathological scars is difficult due to a lack of effective therapeutic options and frequently involves scar revision surgery, which can induce renewed scar formation (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The role of Postn in skin pathologies (Arima, et al, 2015, Crawford, et al, 2015, Mineshige, et al, 2015, Shiraishi, et al, 2012, Song and Qin, 2008, Supp, et al, 2012, Yamaguchi, et al, 2013, Zhang, et al, 2015, Zhou, et al, 2010) and wound healing (Elliott, et al, 2012a, Elliott, et al, 2012b, Jackson-Boeters, et al, 2009, Nishiyama, et al, 2011, Ontsuka, et al, 2012, Walker, et al, 2015, Zhou, et al, 2010) has been the subject of intense research, which has pointed to very specific roles for Postn.…”
Section: Skin Healingmentioning
confidence: 99%
“…Further evidence for the importance of Postn in skin comes from analysis of its expression patterns in scarring (Crawford, et al, 2015, Li, et al, 2013, Song and Qin, 2008, Zhang, et al, 2014, Zhou, et al, 2010) and in direct contrast, non-healing skin lesions (Elliott, et al, 2015). Postn is overexpressed in both hypertrophic and keloid scarring (Crawford, et al, 2015, Zhou, et al, 2010).…”
Section: Skin Healingmentioning
confidence: 99%
“…Periostin is consistently induced in activated myofibroblasts and critically regulates their matrix-synthetic function [96]. Periostin potently stimulates fibroblast proliferation and myofibroblast persistence [97]; whether its stimulatory actions involve intracellular or matricellular effects remains unknown.…”
Section: Matricellular Proteins Regulate Fibroblast Phenotype and Funmentioning
confidence: 99%